Transfer of type II collagen-induced arthritis from DBA/1 to severe combined immunodeficiency mice can be prevented by blockade of Mac-1. - Taylor, P C (1996)
Collagen-induced arthritis in susceptible mice is widely accepted as an experimental model for human rheumatoid arthritis (RA). We have investigated the role of the Mac-1 integrin beta 2 in the development and maintenance of arthritis by means of in vivo administration of 5C6 monoclonal antibody (mAb) to block this receptor. Injection of a single dose of 5C6 mAb (0.5 mg, intraperitoneally) prior to the expected onset of collagen-induced arthritis in DBA/1 mice diminished the severity of subsequent disease in these animals, as assessed both clinically and histologically (P < 0.01, chi 2). In the DBA/1 to severe combined immunodeficiency (SCID) transfer model of arthritis, the incidence of clinical arthritis was significantly reduced in SCID mice receiving maintained 5C6 treatment commencing the day prior to administration of donor splenocytes. Histological evaluation of joints from animals without clinically evident arthritis confirmed the absence of an inflammatory infiltrate in 22/27 joints examined. In a minority of these joints, however, synovial hyperplasia was apparent. In contrast, delaying antibody administration until 10 days after donor spleen cell transfer failed to protect three of five SCID recipients. These results confirm a functional role for Mac-1 in the generation of collagen-induced arthritis in mice. Since mAb 5C6 is non-cytotoxic, its action must be by blockade of the interactions between Mac-1 and its natural ligand(s). Our findings support the hypothesis that cells expressing Mac-1 play an important role in the induction and maintenance of joint damage in collagen-induced arthritis.